Pre-hospital Physical Activity Status Affects In-hospital Course of Elderly Patients with Acute Myocardial Infarction - Takamichi Miyamoto; Tohru Obayashi; Eijirou Hattori; Yasuteru Yamauchi; Akihiro Niwa; Mitsuaki Isobe (Journal of Medical and Dental Sciences, 2010)
Background: The clinical course of elderly patients with acute myocardial infarction (AMI) can sometimes unexpectedly result in an adverse outcome even when therapy appears to be successful. We suspect that specific factors may characterize this worsening of status during hospitalization. Purpose: This study examines whether the pre-hospital physical activity status of the elderly treated with percutaneous coronary intervention (PCI) for AMI affects their in-hospital course. Methods: We studied 110 consecutive patients, aged 80 or older, who had undergone emergent PCI for AMI. Patients were divided into two groups based on clinical presentation: Better Killip class (Killip classes I and II) and Worse Killip class (Killip classes III and IV). Patients were also divided into two groups based on pre-hospital physical activity status, determined retrospectively by review of medical records: Good physical activity (n=57) comprising those able to go out alone independently and Poor physical activity comprising those mainly confined to home (n=53). Results: The overall in-hospital mortality rate was 9.1% for the study population. The Worse Killip class group had a higher in-hospital mortality rate than the Better Killip class group (27.8% vs 5.4%, respectively; p=0.0102). In addition, the Poor physical activity group had a higher in-hospital mortality rate than the Good physical activity group (15.1% vs. 3.5%, respectively; p=0.047). Conclusion: These data suggest that pre-hospital physical activity status in elderly patients with AMI may affect in-hospital mortality as well as Killip class.